<h3>
♫ - - - - - - - - - - - - - - - ~Hello There!~ - - - - - - - - - - - - - - - ♫</h3>
➷ Angle XBC = 55 degrees because corresponding angles are equal
b) We already know angle XBC
Angle XCB = Angle XBC because isosceles base angles are equal
Therefore, angle XCB = 55 degrees
Angles in a triangle equal 180 degrees
180 - (55 + 55) = 70
Angle BXC = 70 degrees
<h3><u>
✽</u></h3>
➶ Hope This Helps You!
➶ Good Luck (:
➶ Have A Great Day ^-^
↬ ʜᴀɴɴᴀʜ ♡
The answer to your question is D.
He must work 13 hours. I don't feel like showing my work.
multiply 14 x 2.54
14 x 2.54 = 35.56 centimeters
By using exponent properties, we will get the simplified expression:
![x^{-1}*y^{1/2}*z^2](https://tex.z-dn.net/?f=x%5E%7B-1%7D%2Ay%5E%7B1%2F2%7D%2Az%5E2)
<h3>
How to simplify the given expression?</h3>
Here we have the expression:
![(x^{1/2}*y^{-1/4}*z)^{-2}](https://tex.z-dn.net/?f=%28x%5E%7B1%2F2%7D%2Ay%5E%7B-1%2F4%7D%2Az%29%5E%7B-2%7D)
Remember the exponent properties:
![(a^n)^m = a^{n*m}](https://tex.z-dn.net/?f=%28a%5En%29%5Em%20%3D%20a%5E%7Bn%2Am%7D)
And:
![(a*b)^n = (a^n)*(b^n)](https://tex.z-dn.net/?f=%28a%2Ab%29%5En%20%3D%20%28a%5En%29%2A%28b%5En%29)
So using these two properties, we can rewrite:
![(x^{1/2})^{-2}*(y^{-1/4})^{-2}*(z)^{-2}\\\\(x^{-2*1/2})*(y^{-2*-1/4})*(z^{-2}})\\\\x^{-1}*y^{1/2}*z^2](https://tex.z-dn.net/?f=%28x%5E%7B1%2F2%7D%29%5E%7B-2%7D%2A%28y%5E%7B-1%2F4%7D%29%5E%7B-2%7D%2A%28z%29%5E%7B-2%7D%5C%5C%5C%5C%28x%5E%7B-2%2A1%2F2%7D%29%2A%28y%5E%7B-2%2A-1%2F4%7D%29%2A%28z%5E%7B-2%7D%7D%29%5C%5C%5C%5Cx%5E%7B-1%7D%2Ay%5E%7B1%2F2%7D%2Az%5E2)
So we conclude that the completely simplified expression is:
![x^{-1}*y^{1/2}*z^2](https://tex.z-dn.net/?f=x%5E%7B-1%7D%2Ay%5E%7B1%2F2%7D%2Az%5E2)
If you want to learn more about exponents:
brainly.com/question/8952483
#SPJ1